Legal Status of Post-Mortem Social Protection Funds in Contemporary Islamic Law: Judicial Reinterpretation of Tirkah in BPJS Death Benefits - Nuraliah Ali; Thea Farina; Ivans Januardi; Hazman Hassan; Arief Budiono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Statement of the Problem: This study aims to analyze the legal status of the death benefit from BPJS Ketenagakerjaan from the perspective of Islamic inheritance law, through judicial interpretation in the Religious Court Decision No. 273/Pdt.G/2024/PA.Plk. Introduction: The focus of the study was to determine whether the benefit constituted part of the inheritance (tirkah) or a specific gift (hibah) to the recipient designated administratively. Method: This study used a normative juridical approach. The primary source was Decision No. 273/Pdt.G/2024/PA.Plk, which was analyzed based on the theory of maqāṣid al-sharī‘ah and the concept of al-māl al-mustafād. Results: BPJS death benefit constitutes part of the tirkah because it originates from the contributions of the deceased during her lifetime. The benefit is not a voluntary gift, but an economic right that must be distributed to all heirs following faraidh law, and cannot be excluded by the administrative designation of the beneficiary. Contribution: This study serves as a reference for judges, academics, and practitioners in handling inheritance disputes involving modern financial instruments, such as insurance, pensions, and social security, within the framework of Islamic law